If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + -2x = 1 Solving -9 + -2x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2x = 1 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = 1 + 9 -2x = 1 + 9 Combine like terms: 1 + 9 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| 4(x+5)=44Whatisx | | 23-5v=4v+5 | | 4w-10=54 | | 8n^2+20n=12 | | -3(x-3)=-2(-2-x) | | 560x(x)=70 | | 7-8x=135 | | 3p^2=3p+6 | | 50x^2+25x-3=0 | | 10k^2-4K-32=-11 | | (m-5)(m-5)=13 | | 4-5/2b=a8-5b | | 4w+5=2w+13 | | 8x-96=-6x+128 | | 3(x+3)=-3(2-x) | | 4/(7-i) | | 5n^2-25=20n | | 2.68x^2+4.75=-2.25 | | 7n^2+39-18=0 | | 9y^3-21y^2-18y=0 | | x^2+7=67 | | (8x^2-2x+7)+(4x^3-4x)=0 | | 31/5x=-7 | | 5x+8+4x+1=180 | | 8-4r=-2-1 | | X÷8/9=21 | | 0.5x+10=54 | | 5m^2-36m+36=0 | | X÷8/8=21 | | 2x+1=6x-7 | | 5b+3=4b | | 4n+5=47-3n |